2015
DOI: 10.1038/ismej.2015.130
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal variation in virus-induced mortality of phytoplankton across the North Atlantic Ocean

Abstract: Viral lysis of phytoplankton constrains marine primary production, food web dynamics and biogeochemical cycles in the ocean. Yet, little is known about the biogeographical distribution of viral lysis rates across the global ocean. To address this, we investigated phytoplankton groupspecific viral lysis rates along a latitudinal gradient within the North Atlantic Ocean. The data show large-scale distribution patterns of different virus groups across the North Atlantic that are associated with the biogeographica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
112
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(124 citation statements)
references
References 96 publications
(110 reference statements)
10
112
1
1
Order By: Relevance
“…For example, increasing viral lysis rates of phytoplankton were recorded from high to low latitudes across the North Atlantic Ocean and, interestingly, correlated positively with temperature and salinity (Mojica et al, 2015). Consistent with this finding, high incidence of lysogeny and low viral lysis rates were shown to occur in low temperature ecosystems such as polar, mesopelagic and deep-sea waters or during cold periods in temperate systems Williamson et al, 2002;Weinbauer et al, 2003;McDaniel et al, 2006;Evans et al, 2009).…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…For example, increasing viral lysis rates of phytoplankton were recorded from high to low latitudes across the North Atlantic Ocean and, interestingly, correlated positively with temperature and salinity (Mojica et al, 2015). Consistent with this finding, high incidence of lysogeny and low viral lysis rates were shown to occur in low temperature ecosystems such as polar, mesopelagic and deep-sea waters or during cold periods in temperate systems Williamson et al, 2002;Weinbauer et al, 2003;McDaniel et al, 2006;Evans et al, 2009).…”
Section: Introductionsupporting
confidence: 59%
“…There is, to our knowledge, no report of actual viral lysis rates in Micromonas natural populations to support our speculation. Nonetheless, a recent study observed a latitudinal variation in virus-mediated mortality of phytoplankton across the North Atlantic Ocean and pointed out a correlation between the velocity of viral lysis and in situ temperature that varied between 10 and 25°C (Mojica et al, 2015). Such geographic partitioning of viral lysis processes could have important consequences for the ecology and the biogeochemistry of the global ocean.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the combination of growth and losses (grazing and viral lysis) could explain the microbial population dynamics observed in this study. It is noteworthy to mention a recent study in the oligotrophic northeastern Atlantic Ocean, which reported a shift from a grazing-dominated to a viral-lysis-dominated phytoplankton community with strengthening vertical stratification (shoaling the mixed layer depth and enhancing nutrient limitation; Mojica et al, 2016). Thus, we highly recommend that future research on OA combine mesocosm studies focusing on changes in microbial community composition and activity with experiments aimed at understanding the effects of OA on food web dynamics, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Microzooplankton grazing and viral lysis of phytoplankton was determined using the modified dilution assay based on reducing grazing and viral lysis mortality pressure in a serial manner allowing for increased phytoplankton growth (over the incubation period) with dilution (Mojica et al, 2016). Two dilution series were created in clear 1.2 L polycarbonate bottles by gently mixing 200 µm sieved whole seawater with either 0.45 µm filtered seawater (i.e.…”
Section: Viral Lysis and Grazingmentioning
confidence: 99%
See 1 more Smart Citation